2006
DOI: 10.1055/s-2006-950425
|View full text |Cite
|
Sign up to set email alerts
|

N-Amino-N-methylmorpholinium Salts: Highly Active Aziridination Reagents for Chalcones

Abstract: A highly effective aziridination reagent, based on Nmethylmorpholine, is reported which effects rapid conversion of chalcones to N-unfunctionalised aziridines at room temperature.Aziridines are highly attractive synthetic intermediates, 2 largely because they can undergo ring opening with a variety of nucleophiles to give functionalised amine products. 3,4 However, alkene aziridination, particularly asymmetric aziridination, is far less well developed than the closely related epoxidation. 5-8 We were attracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…Tertiary alkylamines are generally used as Brønsted bases in organic synthesis 1–2. On the other hand, many reactions are known, where tertiary amines act as nucleophilic catalysts 3–32. 1,4‐Diazabicyclo[2.2.2]octane (DABCO, 1e ) and quinuclidine ( 1f ), for example, are common catalysts in Baylis–Hillman reactions7 and in cyclopropanations of Michael acceptors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary alkylamines are generally used as Brønsted bases in organic synthesis 1–2. On the other hand, many reactions are known, where tertiary amines act as nucleophilic catalysts 3–32. 1,4‐Diazabicyclo[2.2.2]octane (DABCO, 1e ) and quinuclidine ( 1f ), for example, are common catalysts in Baylis–Hillman reactions7 and in cyclopropanations of Michael acceptors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A possible general mechanism involving the N-N ylide is proposed to satisfactorily elucidate the generation of Ketoaziridines. A comparison of this procedure with previous work [24][25][26][27][28][29] on the synthesis of N-H ketoaziridines shows that simple one-pot, not expensive starting material and easy workup are the advantage of this direct N-H insertion method.…”
Section: Resultsmentioning
confidence: 90%
“…The search for the direct aziridination of olefins to prepare N-unsubstituted aziridines is currently an attractive field of research [24][25][26][27][28]. Despite work reported on the synthesis of ketoaziridines, novel and widely applicable methods for the synthesis of them are still in demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 We have found that chiral hydrazinium salts may be easily prepared and isolated from our binaphthylderived amines. For example, we were able to prepare hydrazinium salt (S)-23 from amine (S)-5 in 77% yield simply by stirring the tertiary amine with 1.1 equivalents of DppONH 2 in dichloromethane overnight; filtration then gave the pure salt (S)-23 (Scheme 7).…”
Section: Scheme 6 Development Of Hydrazinium Saltsmentioning
confidence: 96%